Classical and Modern Polyglot Language Learning Models - Zaky, Ahmad; Ritonga, Ade Muhammad (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2024)
This study discusses Language Learning applied by Polyglots, this study is important to discuss for foreign language learning developers, because polyglots are able to learn many languages effectively and efficiently, Polyglots have a different language learning model from language learning in general, polyglots have their own approaches, methods and techniques. The focus of the research on classical and modern polyglots who are the objects of research and will be discussed in this paper, they are people who master many languages, classical and modern polyglots master many languages in different ways, of course this is interesting to study. . This paper is a qualitative study using the content analysis method which aims to produce an objective and systematic description of the content, as well as identify patterns, themes, concepts and models in it, content analysis is used because there is sufficient digital data on the internet to answer this research question, This study will answer the question of how the language learning model implemented by classical and modern polyglots, The results of the study are expected to be applied to modern foreign language learning and produce a new learning model that is able to achieve optimal foreign language learning.